The Book of Timothy : The Devil, My Brother, and Me - Wilson, Joan Nockels, 1964- (Book collections on Project MUSE., 2021)
"Set in Rome, Chicago, and Anchorage, and spanning thirty years from crime to confrontation, The Book of Timothy: A Sister's Pursuit recounts in lyric movements a sister's journey, partly through trickery, but eventually through truth, to gain a long-absent admission from the priest who abused her brother. While on that journey, Nockels Wilson, a former prosecutor, confronts not only the priest, but her personal quest for vengeance. She further seeks an understanding of how the first Book of Timothy, the work of St. Paul, contributed to the silencing of women in her once loved Catholic Church. This Book of Timothy promises to take the reader on a quest for justice and down a path of unexpected coincidences that ends where it first began: out of a great love for a brother and in the power of first memory"--